CAP/EOM-CCSD method for the study of potential curves of resonant states - Ghosh, Aryya; Karne, Anagha S.; Pal, Sourav; Vaval, Nayana (Physical Chemistry Chemical Physics, 2013)
The equation-of-motion coupled-cluster (EOM-CC) method along with the complex absorbing potential (CAP) is used for the study of resonance in e(-)-N-2 and e(-)-CO. Resonance position and width are studied as a function of bond length. We report the potential curves (PC) of the resonance states.